IMPLEMENTASI KEUANGAN SYARIAH DALAM KOPERASI: SOLUSI INOVATIF BAGI KOPERASI PEMBERDAYAAN EKONOMI UMMAT DAARUT TAUHID - Achmad Ludvy; Arif Hidayat; Muhamad Badru Zaman (Abdi Jurnal Publikasi, 2025)
Cooperatives play a strategic role in strengthening the people's economy, especially when run based on sharia principles that prioritize justice, transparency, and blessings. This community service activity aimed to provide education and assistance in implementing a sharia financial system at the Daarut Tauhid Community Economic Empowerment Cooperative, held on April 19–20, 2025. The activity methods included counseling, training, simulations, and the development of a draft SOP for sharia finance. The results of the activity demonstrated a significant increase in the understanding of cooperative administrators and members regarding sharia financial concepts and practices, including basic skills in recording sharia transactions and a commitment to institutional transformation. This activity confirmed that with a contextual educational approach, community-based cooperatives have the potential to transform into superior and sustainable sharia microfinance institutions. Follow-up efforts in the form of further training, SOP refinement, and system digitization are needed to ensure the comprehensive and effective implementation of sharia finance.